The Constitutional Law of the People’s Republic of China and Its Development - Jihong, Mo (Columbia Journal of Asian Law, 2009)
The People’s Republic of China (PRC) has seen the enactment of several constitutional documents. These are the Constitutions of 1954, 1975, 1978, and 1982. The 1954 Constitution confirmed the basic governmental system, including the structure of state organs and citizens’ rights. The 1975 and 1978 Constitutions were influenced by the extreme leftist sentiments of the Cultural Revolution, which promoted a theory of continuing revolution under proletarian dictatorship, inconsistent with the basic principles of modem constitutionalism. The Constitution currently in effect was enacted in 1982. Through a series of amendments,1 constitutionalist principles such as rule of law, democracy and protection of human rights have been incorporated, and the resulting Constitution is a relatively complete constitutional text. [1] The 1982 Constitution has been amended four times, in 1988, 1993, 1999, and 2004.